Implementasi Pembelajaran Sejarah Dengan Nilai-Nilai Keislaman di MAN 1 Medan - Daulay, Mawarda; Sumantri, Pulung; Nababan, Surya Aymanda (Ilmu Bersama Center, 2024)
The results of the research show that the implementation of Islamic values in history learning at MAN I Medan includes: (1) The process of planning history learning with Islamic values at MAN I Medan, to integrate Islamic values into the subject history at MAN I Medan Teachers must design lesson plans and choose the right materials and methods so that the learning process runs effectively and efficiently Understanding Islamic values in history learning at MAN I Medan, to increase the students' understanding of Islamic values that are integrated in history learning. These values must be linked to Islamic values related to the events that occur in everyday life, (2) Implementation of history learning with Islamic values at MAN 1 Medan, teachers must consider several things before implementing history learning with Islamic values at MAN 1 Medan And how teachers can take the advantage of question and answer discussions with the students about Islamic values which are explained in the material of the subject, (3) Understanding Islamic values in history learning at MAN I Medan, to increase the students' understanding of Islamic values that are integrated in history learning. These values must be linked to Islamic values related to the events that occur in everyday life, (4) Obstacles and efforts which are made to integrate history learning with Islamic values at MAN I Medan. Lack of the teachers' understanding of Islamic values which are relevant to the historical material, lack of the appropriate learning resources and teaching materials, and lack of encouragement and desire of the students to learn.